Necessary, yet mistreated: the lived experiences of black women essential workers in dual pandemics of racism and COVID-19. Issue 3 (3rd September 2022) - Goode, Rachel W.; Schultz, Kevan; Halpern, David; Godoy, Sarah; Goings, Trenette Clark; Chapman, Mimi
ABSTRACT: The COVID-19 pandemic has showcased the United States' reliance on essential workers, or those deemed necessary to continue critical societal functions. Black women remain overrepresented in essential positions and are on the frontlines of two pandemics: COVID-19 and racism. Using a phenomenological research design, we conducted semi-structured interviews to examine the experiences of 22 Black women essential workers navigating these dual pandemics. Salient themes of these experiences included: desire to and fear of protest; navigating extreme emotions; mixed levels of understanding from colleagues; and a rise in blatantly racist confrontations in the workplace. Further reflection is needed to understand the complex dynamics these women faced.